Dependência econômica e inadimplência : alternativas femininas para a sobrevivência após o divórcio (Vitória/ES, 1977-1988) - Mattos, Cristiane Araújo de (2008)
Using the contrast between Oral history and documentary research, redeem particularities from family relations between men and women submitted to inedited of the appliance of the Divorce Law in Brazil, from 1977 on. Emphasizes, as temporal parameter, the promulgation of the Federative Republic Constitution of Brazil, on 1988, that imputed the women with a equality condition with the men never before experimented by the Brazilian Legislative System. A period strongly marked by debates about the effective contribution of women as agents of social transformations, the temporal timeline exhibits economic, juridical and social transformations of great importance to the genre studies, specialty because it merge approaches from law, history and education inside a context that analyses the maintenance of social behavior assigned to men and women even in the face of the massification of the new standards. The directioning of the women to the business area didn’t exempt her from her duties of home maintenance and child education, imputing in an overcharge of functions that now includes the financial family sustenance. In spite of reoccurring, this model of female behavior, today recognizable at large scale, doesn’t show satisfactory to every individual, allowing coexistence of women that direct themselves to the business area with those who still direct themselves to marriage, precept largely disseminated by education until mid XX century. Based on sexism, as much in formal education as in informal education from men and women, reinforced precepts of biological differentiation that deviated from reality exhibited by women professionalization that, although diverging, grounded the maintenance of a diffusing a unequally legislation until the end of that century. The legal recognition of equality between men and women didn’t caused, nevertheless, immediate change of behavior, allowing that the notion assimilated by the androcentric socialization process remained intact, despite undeniable adaptations. The interviews analysis and judicial documents show the survival of a female conduct model formerly dominating and that, respecting the particularities of each historic period, can reinforce themselves to the point of becoming fully visible, no more as a lonely model, but as an alternative to the now existent models of social women performance.